Implementasi Axioo Class Program Berdasarkan Relevansi Incheon Declaration Dalam Memajukan Pendidikan SMK di Indonesia - Alfons Kristianto (Global Political Studies Journal, 2021)
Abstract Various educational problems hinder the development and progress of the nation. A global forum, namely the World Education Forum (WEF) 2015 was held as an effort to formulate solutions and strategies for advancing education with a target in 2030. WEF 2015 also produced the Incheon Declaration as a education observer actors’ commitment and seriousness to advance education. Indonesia is a country that attended WEF 2015 when at the same time have been experiencing problems in its education sector, especially vocational education (SMK). Mabito Karya Indonesia Company is a private company actor that is serious in advancing vocational education in Indonesia through the implementation of the Axioo Class Program. All efforts in the Axioo Class Program are implicitly aligned with the articles of the Incheon Declaration.The implementation of the Axioo Class Program also involves various local and international actors. This research uses narrative analysis method in qualitative research method. This study concludes the importance of synergy in efforts to advance vocational education in Indonesia with the Incheon Declaration as global development ideas so that educational progress can be successfully realized. Keywords : Axioo Class Program, Incheon Declaration, Advancing Vocational Education (SMK), Mabito Karya Indonesia Company, WEF 2015